Olivia - Falconer, Ian, 1959-2023. (New York : Scholastic Inc., 2001)
Whether at home getting ready for the day, enjoying the beach, or at bedtime, Olivia is a feisty pig who has too much energy for her own good.
"Caldecott honor book"--Cover.
Keywords: Swine -- Fiction; Behavior -- Fiction